Immediate and long-term results of radiation therapy in combination with capecitabine and oxaliplatin in the treatment of patients with asquamous cell carcinoma of the anus - A. A. Nevolskikh; Y. Y. Mihaleva; V. A. Avdeenko; L. N. Titova; T. P. Berezovskaya; I. A. Gulidov; L. O. Petrov; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал, 2023)
Introduction. The current standard of care is concurrent radiation therapy (RT) and chemotherapy with mitomycin or cisplatin in combination with fuoropyrimidine drugs. One possible option for effective chemotherapy regimens with a lower toxicity is the combination of oxaliplatin and capecitabine with RT. The purpose of the study: a retrospective evaluation of the results of combined treatment of 74 patients with squamous cell carcinoma of the anus (SCCA) with the use of oxaliplatin and capecitabine. Material and Methods. The study included 74 patients (men – 12.2 %, women – 87.8 %) with stage I–III SCCA. All patients underwent megavolt photon RT (2×25), a cumulative dose of 50 Gy and a boost of 10 Gy to the anal canal. From days 1 to 14 and from days 22 to 36 of RT, capecitabine was administered orally at a dose of 825 mg/m2  twice a day in combination with intravenous administration of oxaliplatin 50 mg/m2  on days 1, 8, 22, and 29 of RT. If a residual tumor 6 months after completion of chemoradiotherapy was found, patients underwent surgery. Results. All 74 patients underwent RT with a cumulative dose of 60 Gy. Chemotherapy, according to the protocol, was completed in 58 (78.4 %) patients. Grade 3-4 toxicity was noted in 11 (14.9 %) patients. In 64 patients (86.5 %), a complete clinical response was registered. At least one late radiation side effects according to the RTOG (LENT SOMA) scale was noted in 48 (98.0 %) patients, including grade 3-4 complications in 12 (24.5 %) patients. With a median follow-up of 40 months (3-82) cumulative three-year local recurrence rate, overall and relapse-free survival were 15.3 ± 4.5 %, 73.7 ± 5.7 % and 53.5 ± 6.4 %, respectively. Conclusion. Combined treatment of SCCA, based on the combination of RT with chemotherapy with oxaliplatin and capecitabine, is feasible and has acceptable acute toxicity. Additional clinical studies are needed using this chemotherapy regimen in combination with modern RT techniques.